Habitat use and sex-specific foraging behaviour of Adélie penguins throughout the breeding season in Adélie Land, East Antarctica - Widmann, Michel; Kato, Akiko; Raymond, Ben; Angelier, Frédéric; Arthur, Benjamin; Chastel, Olivier; Pellé, Marie; Raclot, Thierry; Ropert‐coudert, Yan (Movement Ecology, 2015)
International audience Background: Marine predators are ecosystem sentinels because their foraging behaviour and reproductive successreflect the variability occurring in the lower trophic levels of the ecosystem. In an era of environmental change,monitoring top predators species can provide valuable insights into the zones of ecological importance that needto be protected. In this context, we monitored the Adélie penguin (Pygoscelis adeliae) as a bio-indicator nearDumont d’Urville, an area of the East Antarctic sector currently being considered for the establishment of a MarineProtected Area (MPA), using GPS-based tracking tags during the 2012/13 austral summer breeding season.Results: The habitat use and foraging areas of the penguins differed by breeding stage and sex and were stronglyassociated with patterns in bathymetry and sea-ice distribution. The first trips, undertaken during the incubationphase, were longer than those during the guard phase and were associated with the northern limit of the sea-iceextent. During the guard phase, birds strongly depended on access to a polynya, a key feature in Antarctic marineecosystem, in the vicinity of the colony. The opening of the ice-free area was synchronous with the hatching ofchicks. Moreover, a sex-specific use of foraging habitat observed only after hatching suggests sex-specificdifferences in the diet in response to intra-specific competition.Conclusions: Sea-ice features that could be affected by the climate change were important factors for the use offoraging habitat by the Adélie penguins. The extent of the foraging area observed in this study is congruent withthe area of the proposed MPA. However, both penguin behavior and their environment should be monitoredcarefully.